SUSTAINABILITY PRACTICES, PROFITABILITY AND FIRM VALUE: EVIDENCE FROM INDONESIA’S FOOD AND BEVERAGE INDUSTRY - Ika Suci Indriana; Putri Puspita Ayu (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study examines the effect of Green Accounting, Carbon Emission Disclosure, Environmental Performance, and Profitability on Firm Value in food and beverage firms listed on the Indonesia Stock Exchange during 2022–2024. While prior studies report inconsistent findings, limited attention has been given to how sustainability-related information is interpreted by investors in emerging markets, particularly under conditions where sustainability disclosures may generate different market responses. This indicates a gap in understanding the conditional role of sustainability practices in firm valuation. This research applies a quantitative approach using secondary data sourced from annual reports, sustainability reports, and PROPER ratings, while being conceptually framed by Legitimacy Theory and Signaling Theory. The data are analyzed using multiple linear regression. The findings indicate that Green Accounting and Profitability positively influence Firm Value, while Carbon Emission Disclosure has a negative effect, and Environmental Performance does not exhibit a significant impact. These findings suggest that sustainability-related disclosures are interpreted selectively by investors based on their perceived economic relevance and credibility, indicating that such disclosures may not always function as effective positive signals. This study contributes to the literature by highlighting the conditional nature of sustainability practices in influencing firm value, particularly in emerging markets experiencing declining firm valuation trends. Practically, the findings suggest that firms need to align sustainability initiatives with financial performance, while regulators should enhance the credibility and standardization of sustainability disclosures to reduce investor skepticism.